Combining ranibizumab with calcium dobesilate to reduce injection frequency in diabetic macular edema treatment - Chen, Jian-Ying; Pan, Hong-Wei; Zhang, Xiao-Ming; Liu, Jing-Min; Chan, Sum-Yuet; Liu, Ting-Ting; Ma, Jian-yi; Liu, Qi; Yi, Wan-Zhao; Wu, Ya-Ni; Gu, Shuo-Shuo; Xia, Ling-Xiao; et al. (International ophthalmology, 2025)
Background This study explores the potential of calcium dobesilate combined with intravitreal ranibizumab injections to reduce the treatment frequency in patients with DME-induced visual impairment and observes the clinical outcomes. Methods In this investigation involving 90 DME patients, a comparative analysis was conducted between a group treated with both ranibizumab injections and calcium dobesilate capsules (45 patients) and a control group receiving only the injections (45 patients). Treatment was monthly for 3 months, then adjusted as needed, with a follow-up at 12 months focusing on injection frequency, BCVA scores, and CMT to assess both treatment efficacy and safety. Results In the 12-month trial, subjects receiving a new combination therapy experienced fewer required intravitreal injections (average 4.73) compared to those on standard monotherapy (average 6.02), showing a significant reduction ( p < 0.05). Final assessments revealed substantial improvements in best corrected visual acuity (BCVA) and central macular thickness (CMT) for both groups from baseline ( p < 0.05). The experimental group notably showed greater enhancements in BCVA and CMT, highlighting the superior effectiveness of the combination therapy in managing DME symptoms with reduced treatment frequency. Conclusion Combination therapy with calcium dobesilate and ranibizumab decreased the frequency of intravitreal injections and led to greater improvements in BCVA and CMT compared to ranibizumab alone over 12 months. Both treatments were well-tolerated, with the combination therapy demonstrating a favorable safety profile.